An introduction to the passage of energetic particles through matter - Carron, N. J. (Taylor & Francis, 2011)
Identifying where to access data, extracting a needed subset from available resources, and knowing how to interpret the format in which data are presented can be time-consuming tasks for scientists and engineers. By collecting all of this information and providing a background in physics, An Introduction to the Passage of Energetic Particles through Matter enables specialists and nonspecialists alike to understand and apply the data.